Multidimensional role of adapalene in regulating cell death in multiple myeloma - Cao, Xinya; Xiang, Jie; Zhang, Qi; Liu, Jinwen; Zhou, Dongming; Xu, Yong; Xu, Peipei; Chen, Bing; Bai, Hua (Frontiers in Pharmacology, 2024)
Aims: Multiple myeloma (MM) remains a challenging condition to cure, with persistent drug resistance negating the benefits of treatment advancements. The unraveling complexities in programmed cell death (PCD), inclusive of apoptosis, autophagy, and ferroptosis, have highlighted novel therapeutic avenues. Our study focuses on deciphering how adapalene (ADA), a small molecule compound, accelerates the demise of MM cells via targeting their compensatory survival mechanisms. Methods: To assess the impact of ADA on MM, we employed flow cytometry and trypan blue exclusion assays to determine cell viabilities across MM cell lines and primary patient samples post-treatment. To delineate ADA's therapeutic targets and mechanisms, we conducted RNA sequencing (RNA-seq), gene set enrichment analysis (GSEA), molecular docking, and molecular dynamics simulations. We further designed pre-clinical trials emphasizing MM, exploring the efficacy of ADA as a standalone and in combination with bortezomib (BTZ). Results: ADA elicited a dose-responsive induction of MM cell death. Building upon ADA's anti-MM capabilities as a single agent, we proposed that ADA-BTZ co-treatment might amplify this lethality. Indeed, ADA and BTZ together greatly potentiated MM cell death. ADA proved beneficial in restoring BTZ susceptibility in BTZ-resistant relapsed or refractory MM (RRMM) patient cells. Molecular simulations highlighted ADA's high affinity (-9.17 kcal/mol) for CD138, with MM-GBSA revealing a binding free energy of -27.39 kcal/mol. Detailed interaction analyses indicated hydrogen-bonding of ADA with CD138 at the Asp35 and Gln34 residues. Additionally, ADA emerged as a versatile instigator of both ferroptosis and apoptosis in MM cells. Furthermore, ADA disrupted activation of the nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB) pathway triggered by BTZ, fostering cell death in BTZ-resistant MM subsets. Conclusion: ADA demonstrates a comprehensive capability to orchestrate MM cell death, exerting pronounced anti-MM activity while disrupting NF-κB-related drug resistance. ADA sensitization of MM cells to BTZ unravels its potential as a novel therapeutic drug for MM management.